The Effect of Stellar Evolution on Dispersal of Protoplanetary Disks: Disk Fraction in Star-forming Regions - Ayano Komaki; Naoki Yoshida (The Astrophysical Journal)
We study the effect of stellar evolution on the dispersal of protoplanetary disks by performing one-dimensional simulations of long-term disk evolution. Our simulations include viscous disk accretion, magnetohydrodynamic winds, and photoevaporation as important disk dispersal processes. We consider a wide range of stellar mass of 0.1–7 M _⊙ and incorporate the luminosity evolution of the central star. For solar-mass stars, stellar evolution delays the disk dispersal time as the far-ultraviolet (FUV) luminosity decreases toward the main sequence. In the case of intermediate-mass stars, the FUV luminosity increases significantly over a few million years, driving strong photoevaporation and enhancing disk mass loss during the later stages of disk evolution. This highlights the limitations of assuming a constant FUV luminosity throughout a simulation. Photoevaporation primarily impacts the outer regions of the disk and is the dominant disk dispersal process in the late evolutionary stage. Based on the results of a large set of simulations, we study the evolution of a population of star–disk systems and derive the disk fraction as a function of time. We demonstrate that the inclusion of stellar luminosity evolution can alter the disk fraction by several tens of percent, bringing the simulations into closer agreement with recent observations. We argue that it is important to include the stellar luminosity evolution in simulations of the long-term dispersal of protoplanetary disks.